Online Instruction in Relation to Student Satisfaction in Higher Education at Tribhuvan University, Nepal (Journal of Population and Development, 2023)
During the pandemic of COVID-19 like in other educational institutions, Tribhuvan University also shifted its instructional mode from face-to-face to online mode. However, limited access and proficiency to technology, receiving timely feedback and communication, working familiarity, and distance among colleagues, teachers and faculties are the main challenging factors of effective online class participation. With this consideration, this paper aimed to identify the effectiveness of online instruction on class participation of Post-Graduate students at Tribhuvan University. In this study, the correlation research design was applied within the positivist philosophical background. From the 5948 population of this study, who participated in the online mode of instruction during the pandemic period, four hundred students were randomly assigned. Semi[1]structured questionnaires are administered through self reporting method. The logistic regression was applied to identify the relationship between classroom effectiveness through online instruction. The result shows those students' learning facilities, technical skills, satisfaction, teachers’ support, and feedback systems have a significantly better effect on online class participation. Unexpectedly students with little support from teachers, no clear direction for work, and a neutral perception than a good perception have applied better e-resources. Technological skills, e-materials, and good perception have not acquired satisfactory results in online instruction. This study concludes that online instruction has not significantly notable effects on students’ class participation. These findings could be considered while making the training package interventions indented to transform basic skills, supportive and related behaviour.